2008
DOI: 10.1007/s00268-008-9656-z
|View full text |Cite
|
Sign up to set email alerts
|

Clinical, Radiological, and Manometric Profile in 145 Patients with Untreated Achalasia

Abstract: These results show that in patients with untreated achalasia: (1) dysphagia was the most frequent complaint, but regurgitation and heartburn were frequently present; (2) a diagnosis of GERD based on the presence of heartburn was highly unreliable; (3) the LES was hypertensive in less than half of patients; and (4) the prevalence, severity, and duration of chest pain did not correlate with the manometric finding of vigorous achalasia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
101
0
7

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 163 publications
(110 citation statements)
references
References 21 publications
2
101
0
7
Order By: Relevance
“…However, the analysis of pH monitoring tracings in all seven patients showed that the abnormal scores were induced by false reflux. 8 Otherwise, among those with a normal reflux profile, a primary esophageal motility disorder such as achalasia or diffuse esophageal spasm occurred in 18% of patients. 24 Patti et al 7 demonstrated that DeMeester scores were abnormal in 14 out of 40 achalasia patients for whom preoperative ambulatory pH was performed.…”
Section: Does Reflux Occur In Achalasia?mentioning
confidence: 97%
See 2 more Smart Citations
“…However, the analysis of pH monitoring tracings in all seven patients showed that the abnormal scores were induced by false reflux. 8 Otherwise, among those with a normal reflux profile, a primary esophageal motility disorder such as achalasia or diffuse esophageal spasm occurred in 18% of patients. 24 Patti et al 7 demonstrated that DeMeester scores were abnormal in 14 out of 40 achalasia patients for whom preoperative ambulatory pH was performed.…”
Section: Does Reflux Occur In Achalasia?mentioning
confidence: 97%
“…According to a previous report, proton pump inhibitors were prescribed to 53% of achalasia patients, histamine H 2 blockers to 10%, and both to 6% on the assumption that GERD was the cause of heartburn and regurgitation. 8 Dysphagia occurs in patients with achalasia and is not easily recognized by patients and physicians. 9 Spechler et al 10 demonstrated that in some patients, the dissolution of heartburn and regurgitation and appearance of dysphagia could be a symptom of achalasia.…”
Section: Overlap Between Gastroesophageal Reflux Disease and Achalasiamentioning
confidence: 99%
See 1 more Smart Citation
“…The prevalence of heartburn in our patients with achalasia was 59.4%, which is higher than that reported elsewhere. [9][10][11] It is generally thought that the diagnosis of GERD can be reliably made on the basis of clinical symptoms: if a patient has heartburn or regurgitation it is assumed that acid reflux is present, and therefore a PPI is prescribed. However, symptoms are less sensitive and specific than commonly believed.…”
Section: Discussionmentioning
confidence: 99%
“…9 기저 하부식도괄약근 압력의 증가, 기저 식 도체부의 안정 시 압력증가, 연동파의 동시수축은 achalasia 진 단에 있어 보조적인 소견이며, 임상적으로 achalasia로 진단했 던 환자의 50%가 기저 하부식도괄약근 압력의 증가 소견이 없 는 것으로 보고되었다. [10][11][12] 식도체부의 무연동증과 불완전한 하 부식도 괄약근 이완소견을 가진 achalasia의 아형과 완전한 하 부식도 괄약근의 이완을 가진 achalasia의 아형은 드물지만 보 고된 바 있다. 13 …”
Section: 식도내압검사unclassified